DAMPAK PERLAKUAN PEMANASAN INOKULUM TANAH TERHADAP KEMAMPUAN EKTOMIKORIZA UNTUK MENGKOLONISASI AKAR Shorea javanica - Melya Riniarti; Anggraini Eka Wahyuni; Surnayanti Surnayanti (Universitas Lambung Mangkurat, 2017)
Shorea javanica was a high dependent plant to ectomycorrhizal symbiosis, dealing with its growth. In Lampung Province, S.javanica standing stock have been hundreds of years, known as repong damar. It's threatened by some deforestation, such as forest fire. This study aimed to analyze the impact of heating on the ability of ectomycorrhizal colonization and analyze the effect of ectomycorrhizal inoculation on the growth of S. javanica. The experiment arranged by randomized complete design with 5 treatments, which were without inoculum, unheated inoculum, soil inoculums heat to 40oC, 70oC and 100°C for 24 hours. Soil inoculums are taken under S. javanica standing, at Krui, Pesisir Barat District, Lampung Province. The result analyzed by ANOVA and continued with LSD test. The experiment was conducted for four months. The results show that colonization ectomycorrhiza still existed up to 100oC and ectomycorrhiza could enhance growth variables, including height, leaves number, leaf area, root length and root dry weight. The best colonization and growth were on 100oC heating. The heat treatments seem killed some fungus. Only a few fungi could resist and colonize S. javanica roots. Without any competitors, the resist ectomycorrhizal could develop broadly.